Effect of cold atmospheric pressure He-plasma jet on DNA change and mutation - C. Yaopromsiri (2018)
© 2015 Elsevier B.V. Cold atmospheric pressure plasma jet (CAPPJ) effect on DNA change was studied for assessment of its safety. The experiment utilized a home-developed CAPPJ using 100% helium to directly treat naked DNA plasmid pGFP (plasmid green fluorescent protein). A traversal electric field was applied to separate the plasma components and both dry and wet sample conditions were adopted to investigate various factor roles in changing DNA. Plasma species were measured by using optical emission spectroscopy. DNA topological form change was analyzed by gel electrophoresis. The plasma jet treated DNA was transferred into bacterial Escherichia coli cells for observing mutation. The results show that the He-CAPPJ could break DNA strands due to actions from charge, radicals and neutrals and potentially cause genetic modification of living cells.